Moderate Aerobic Exercise May Reduce Metabolic Syndrome Induced Testicular Oxidative Stress and Deterioration in Sperm Parameters - Karaman, Muhammed Emre; Arslan, Cengiz; Gursu, Mehmet Ferit; Gungor, Halil Ibrahim; Arkali, Gozde; Yuce, Abdurraif; Turk, Gaffari (Sciencedomain Int, 2021)
Aims: Studies on testicular oxidative stress, sperm density, motility and morphology of exercise applications in the case of metabolic syndrome is limited. In the present study, it was aimed to investigate the effects of aerobic and anaerobic exercise applications on sperm parameters and testicular oxidative stress parameters in metabolic syndrome induced rats. Study Design: Controlled Trial. Place and Duration of Study: Firat University Experimental Research Center, Elazig/Turkey. Methodology: A total of 24 male Wistar-Albino rats were used in the study. For inducing the metabolic syndrome, 30% fructose solution was prepared fresh every day and administered ad-libitum through the drinking water of the animals. The rats were divided into 4 groups (G1: Control, G2: Metabolic Syndrome, G3: Metabolic Syndrome + Aerobic Ex., G4: Metabolic Syndrome + Anaerobic Ex.). Exercise practices continued 3 days in a week for 6 weeks. Results: Sperm concentrations of G2 and G4 were statistically significantly lower than the control group. The abnormality percentage of G4 was statistically significantly higher than the other groups in terms of head abnormality and total abnormality. MDA level of G2 was statistically significantly higher than the other groups, while GSHpx and catalase levels were low. Conclusion: It can be said that metabolic syndrome may cause oxidative damage in testicular tissue and deterioration in sperm parameters. Moderate-intensity aerobic exercise reduces the deterioration in sperm parameters by creating a protective response against oxidative damage.
Keywords: Aerobic exercise; anaerobic exercise; metabolic syndrome; testis oxidative stress; sperm parameters